Study of knowledge, attitude and practice about polycystic ovarian syndrome among PCOS patients - S. R., Ranjana; B. S., Sreelekshmy; Babu, Bincy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Polycystic ovarian syndrome (PCOS) is a common endocrine disorder with hormonal imbalance affecting the reproductive age. Adequate knowledge and attitude play a vital role in practice of disease. This study was conducted to assess the knowledge, attitude and practice about polycystic ovarian syndrome among PCOS patients in south Kerala. Methods: This was a hospital based descriptive study carried out among PCOS patients in a tertiary care hospital for a period of 4 months which included data collection. The 200 subjects were classified based on inclusion and exclusion criteria out of which 38 subjects were lost to follow up hence a total of 162 patients were included in the study. Results: Majority of subjects had good knowledge (85.8%), attitude (69.8%) and practice (53.7%) towards the PCOS. There was a statistically significant association between knowledge towards PCOS and demographic characteristics (education) and there is also significance in case of association between attitude and education. Hence, there is no association between practice and demographic details. The knowledge and attitude, knowledge and practice, attitude and practice were found to have a positive association between them towards PCOS. There was no link between age groups and medication adherence levels. Conclusion: The presents study provides variable insights into the knowledge, attitude and practice towards PCOS among PCOS patients, offers guidance and resource for the future study. The healthcare providers should consider effective communication with PCOS patients. These findings help in implementing awareness towards PCOS and its early detection.